The association between perioperative risk factors and the method of anaesthesia, and maternal and neonatal outcomes following caesarean delivery in Africa: a sub-study of a 7-day prospective observational cohort study - Gerber, Carmen (Department of Anaesthesia and Perioperative Medicine, 2023)
Background Maternal and neonatal mortality is high in Africa. The African Surgical Outcomes Study found that maternal mortality following caesarean delivery in Africa is 50 times higher than in highincome countries, and independently associated with obstetric haemorrhage and anaesthesia complications. Methods A sub-study was conducted of a seven-day, international, prospective, observational cohort study of patients undergoing caesarean delivery in Africa. The aims were to determine the association between preoperative risk factors and the method of anaesthesia, and to examine the association between method of anaesthesia and i) pre- and post-delivery hypotension, ii) severe anaesthesia complications, iii) maternal mortality, and iv) neonatal mortality. In addition, the association was examined between pre-delivery intraoperative hypotension and neonatal outcomes. The primary outcomes were maternal and neonatal in-hospital mortality censored at 30 days. Secondary outcomes were a composite of four severe anaesthesia complications, the association between method of anaesthesia and intraoperative hypotension, and that between hypotension and neonatal outcomes. Findings 3709 patients who received spinal (2968, 80%) or general anaesthesia (GA) (741, 20%) were recruited from 183 hospitals in 22 African countries from February to May 2016. Maternal mortality was higher with GA than spinal anaesthesia (11/729, 1.5%, versus 9/2881, 0.3%, p = 0.001), as was neonatal mortality (65/662, 9.8% versus 73/2669, 2.7%, p < 0.001). Independent predictors of GA as the method for caesarean delivery included gestational age, American Society of Anaesthesiologists (ASA) category, emergency surgery, eclampsia, placenta praevia, placental abruption, and ruptured uterus. Spinal anaesthesia was administered to 48/94 (51.1%) patients with eclampsia, 12/28 (42.9%) with cardiac disease, 14/19 (73.7%) with preoperative sepsis, 48/76 (63.2%) with antepartum haemorrhage, 30/55 (54.5%) with placenta praevia, 33/78 (42.3%) with placental abruption and 12/29 (41.4%) with a ruptured uterus. There was no association between method of anaesthesia and intraoperative hypotension. There was no association between pre-delivery hypotension and neonatal mortality, cardiopulmonary resuscitation, or Apgar scores at 1 and 5 minutes. Conclusion Analysis of a large cohort of patients undergoing anaesthesia for caesarean delivery in Africa, showed that a larger proportion than in high-income countries received GA, and indicated which patients were more likely to require GA. GA was associated with maternal mortality, neonatal mortality, and severe anaesthesia complications. Spinal anaesthesia was often administered to patients with eclampsia or at high risk for obstetric haemorrhage. Focussed training in the principles of selection of method of anaesthesia, and specifically in the skills of safe GA, are recommended.